As préexistências na Obra de Eduardo Souto de Moura: o Mercado Municipal de Braga. - Maria João Trigo Santana (2013)
The analysis of Eduardo Souto de Moura's work, proven vast and diverse,allows one to recognize how the respect for the history, the place and thepreexistence has a constant presence throughout his architectural path. To thearchitect, the place to intervene has data attached that defines and characterizesit, it is never an empty space free of preexistences and meanings. Souto deMoura finds in the place and its characteristics the guidelines for a coalescing,conscientious and responsible intervention and he does not see them asrestrictions to the architecture but, instead, as the starting point for the creativeprocess.To understand how this belief influences all his projects, it is importantto observe which antecedents played a key role in his training and in hisunderstanding of these issues. The observation of how the architect tacklesthese themes in some of his works becomes also relevant to understand hisunderstanding of the history, the specificity of each place and the preexistenceas indispensable instruments required to design the project. Although thecircumstances are always distinct from work to work, and consequently alsothe strategies adopted, it is possible to verify the existence of commonalitiesbetween them that reflect how Souto de Moura understands the preexistence.The Braga Municipal Market and its subsequent renovations constitute a workcrowding various interventions with different approaches to the preexistence.Their study demonstrates that Eduardo Souto de Moura sees the preexistencesas inseparable elements of the designing process, assuming them and theplace as operative matter that can be manipulated in order to achieve cohesivearchitectural solutions.